Praktik kerja industri bidang management human resources department Hilton Garden Inn Bali Ngurah Rai airport - Made Bintang Nadiva Prameswari; I Gusti Agung Gede Witarsana (Institute for Advanced Science Social, and Sustainable Future, 2023)
Every organization must, of course, have a workforce who will handle or manage the organization so that the organization's goals can be successfully achieved. Without the role of humans in it, the company network cannot be implemented. Every organization must, of course, have a workforce who will handle or manage the organization so that the organization's goals can be successfully achieved. Without the role of humans in it, the company network cannot be implemented. In this research, the Hilton Garden Inn Ngurah Rai Airport Hotel management scheduled 4 working days and 3 days off a week during this pandemic; in 1 day, the author worked 9 hours with details of 8 hours of work and 1 hour of rest. The Hilton Garden Inn Ngurah Rai Airport Hotel requires all training participants to participate in an Orientation Day, which is held for 1 day at the start of implementing industrial work practices, which aims to provide an introduction to the hotel, such as discussing history, facilities, regulations and knowledge about safety and security. Undergoing this Practical program, the author realized that the author had the opportunity to meet and socialize with workers and was given the trust to complete administrative tasks in the Human Resources department. Seniors kindly shared their insights and knowledge with the author, allowing the author to submit ideas opinions, and think creatively.